Occupational Asthma guidelines: a systematic quality appraisal using the AGREE II instrument. Issue 2 (8th November 2013) - Lytras, Theodore; Bonovas, Stefanos; Chronis, Christos; Konstantinidis, Athanasios K; Kopsachilis, Frixos; Papamichail, Dimitrios P; Dounias, George
Abstract : The quality of guidelines is often modest and highly variable. We searched the Medline database for occupational asthma (OA) guidelines meeting our inclusion criteria and undertook a systematic appraisal of them. Six appraisers independently evaluated these guidelines using the AGREE II (Appraisal of Guidelines, Research and Evaluation II) instrument. Standardised scores for each domain and for overall quality were calculated, as well as intraclass correlation coefficients to assess agreement among appraisers. Seven relevant guidelines were identified. Three were based on a systematic review of the evidence. Most guidelines scored high on the domains 'Scope and purpose' and 'Clarity and presentation', but scores on the other domains were variable. The lowest scores were for 'Applicability', suggesting that guideline developers did not pay sufficient attention to practical problems affecting the implementation of their recommendations. We also observed a trend toward improved scores in guidelines published after 2000. Inter-rater agreement was good for most domains, and particularly for 'Rigour of development'. This domain was most strongly correlated with the overall assessment scores, together with 'Scope and purpose' and 'Editorial independence'. The quality of OA guidelines is variable, both within and across guidelines. There is significant room for improvement, and greater efforts to produce high-quality guidelines are warranted, in order to assist clinical decision-making.